UJI PENGGUNAAN MACAM PUPUK ORGANIK CAIR TERHADAP HASIL KEDELAI - Herawati, Jajuk; ,, Indarwati (JURNAL AGRI-TEK, 2016)
Research purposes want to know the influence of application fertilizer liquid organic (POC) to improve the result soybean. Is hypothesized this research is: (1) kind of POC different can provide growth and the results of soybean different; (2) Various POCdifferent can be applied in the soybean plant. The research was conducted using a randomized block design of one factor by treatment as follows: P1 : Without POC ( Control ), P2 : POC Waste Water Hyacinth, P3: POC waste dregs and skin the sugarcane, P4: POC waste coconut coir, P5: POC waste water hyacinth + manure, P6 : POC sugarcane waste dregs + manure + cocopeat, P7: POC waste coconut coir + cocopeat. Each treatment repeated four times, so that was obtained 28 tenement experiment , by using plants 10 sample every tenement. The research note that the treatment poc dregs cane + manure + cocopeat ( P6 ) give heavy dry seed / swaths better than other treatment, Although no different real the treatment poc dregs cane ( P3 ), So also with the potential of the results, Where p6 able to provide the 2,36 tons / ha was p3 able to give a ton / ha 2,12. While in parameters 1.000 the weight , the treatment poc dregs cane + manure + cocopeat ( P6 ) give 1.000 weight of the best, Although no different treatment real with the provision of waste poc dregs and skin cane (P3) or P5.Keywords: Liquid organic fertilizer, and Soybean Production